RIITESH EFFECT: A HOLISTIC APPROACH TO NEUROLOGICAL WELL-BEING WITH EMPHASIS ON THE PRACTICE OF RIITESH MUDRAA - Sinha, Riitesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Riitesh Effect is a holistic therapeutic framework that integrates Riitesh Mudraa, the Small Heavenly Circuit, and Positive Affirmations to address neurological and emotional well-being. This paper explores the scientific foundations of the Riitesh Effect, emphasizing the practice of Riitesh Mudraa as a core component. By combining ancient Indian hand gestures (hasta mudras) with modern acupressure and neurophysiological principles, Riitesh Mudraa has been shown to support individuals with cerebral palsy, Parkinson’s disease, ADHD, anxiety, and other neurodegenerative disorders . This study presents the structured application of the Riitesh Effect, highlights its therapeutic impact, and discusses future research directions for establishing it as a globally recognized complementary therapy.